MANFAAT PERPUSTAKAAN SEKOLAH BAGI PRESTASI BELAJAR SISWA IPS SMP NEGERI 4 SAMPIT - Mahmu’ddin Mahmu’ddin; Siti Halimah; Ayu Wahyuni (STKIP MUHAMMADIYAH SAMPIT, 2019)
The use of libraries is very necessary in schools as information for completing school assignment, this research was conducted to determine the effect of determine the effect of school library untilization on the achievement of class VIII student achievement on integrated social student subjects in public middle school 4 sampit 2018/2019 academic year. The population in this study were all students VIII of SMP Negeri 4 Sampit which amounted to 264 students, then 40 students were taken sample in this study. The sampling technique used the proposition random sampling . thr data analysis technique used is simple linier regression assisted by SPSS 15. The results of the analysis show that there is a significant influence between the use of the school library on learning achievement in integrated social studies subject in 4 sampit publick middle school 2018/2019 academic year